2017
DOI: 10.4018/ijsi.2017010102
|View full text |Cite
|
Sign up to set email alerts
|

Gaits Classification of Normal vs. Patients by Wireless Gait Sensor and Support Vector Machine (SVM) Classifier

Abstract: Due to the serious concerns of fall risks for patients with balance disorders, it is desirable to be able to objectively identify these patients in real-time dynamic gait testing using inexpensive wearable sensors. In this work, the authors took a total of 49 gait tests from 7 human subjects (3 normal subjects and 4 patients), where each person performed 7 Dynamic Gait Index (DGI) tests by wearing a wireless gait sensor on the T4 thoracic vertebra. The raw gait data is wirelessly transmitted to a near-by PC fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…SVM has a solid theoretical basis and provides more accurate results when compared to other algorithms in many applications. As shown in Figure 4, SVMs use a maximal margin splitter [53]. This splitter represents the most remote control possible up to the sampling point.…”
Section: The Support Vector Machine Methodsmentioning
confidence: 99%
“…SVM has a solid theoretical basis and provides more accurate results when compared to other algorithms in many applications. As shown in Figure 4, SVMs use a maximal margin splitter [53]. This splitter represents the most remote control possible up to the sampling point.…”
Section: The Support Vector Machine Methodsmentioning
confidence: 99%
“…Then, the input sample is categorized into the class of the majority in the k nearest points. Thus, if the training data is {(x 1 ,y 1 ), (x 2 ,y 2 ), …, (x N ,y N )} and x is the feature vector of an input sample, the KNN finds the class of the input sample x using a distance metric [ 41 , 42 ], which in this study is the Euclidean distance given by: (b) Support vector machines (SVMs): It is a supervised learning method [ 43 , 44 ] that works on the principle of transforming the input feature space by a nonlinear transformation to a high-dimensional feature space, and searching for an optimal separating hyperplane for the input classes in this new high-dimensional space [ 45 , 46 ]. With this separating hyperplane, the training data xi with labels yi can be classified so that the minimal distance of each point from the hyperplane is maximized.…”
Section: Identification Of Error Patterns In Eye Gaze Datamentioning
confidence: 99%
“…(b) Support vector machines (SVMs): It is a supervised learning method [43,44] that works on the principle of transforming the input feature space by a nonlinear transformation to a high-dimensional feature space, and searching for an optimal separating hyperplane for the input classes in this new high-dimensional space [45,46]. With this separating hyperplane, the training data xi with labels yi can be classified so that the minimal distance of each point from the hyperplane is maximized.…”
Section: Classification Models: K-nn Svm and Annmentioning
confidence: 99%
“…Most of the related studies achieved the best classification performance by Gaussian SVM classifier [11]. Another study showed classification method by four types of SVM classifiers and achieved the best accuracy rate by employing Linear SVM [16]. Therefore, four different types of SVM including Gaussian SVM and Linear SVM were evaluated in this present study.…”
Section: Introductionmentioning
confidence: 97%